Conceptualization of Public Relations Ethics from Qaul Perspective in the Al-Quran - Monarshi, Evri Rizqi; Praptiningsih, Novi Andayani; Hermansah, Tantan (Magister Komunikasi Universitas Sultan Ageng Tirtayasa, 2024)
This study aims to investigate the Islamic perspective on public relations, the principles of public relations regulated by Islam, and the code of ethics in public relations activities according to Islamic views. This paper adopts a qualitative approach with the literature study method. Meanwhile, several cases that identify communication errors, such as those committed by PT KAI's PR by not being truthful, serve as the main benchmark for the importance of implementing Islamic values in the field of public relations. The researcher found that Islam views public relations as an important part of human life because Islamic values are not only for the hereafter but also serve as guidelines in communication and interaction in the world. The principles of public relations explained in the Quran, known as the six principles of qaul, provide guidance for Muslims to carry out public relations activities with good ethics. Additionally, the code of ethics for public relations derived from the teachings of the Quran and the hadiths of the Prophet Muhammad (PBUH) serves as the foundation for moral and ethical public relations practices. The conclusion of this study is that the values and principles of Islam in public relations activities are believed to provide success, achievement, and blessings in these activities. This can also prevent humans from the damage and chaos that may arise from uncontrolled communication. Therefore, public relations practices based on Islamic values are expected to lead humans to safety in this world and the hereafter. Keywords: Islam, Public relations, Al-Quran, Qaul.